Their Two Cents Worth': Exploring User Agency in Readers” Comments in Online News Media - Vadratsikas, Konstantinos; Papa, Venetia; Milioni, Dimitra L. (My University, 2012)
This paper explores the assumption that user-generated content in mass media websites gives audiences greater power over influencing news making. Employing a content analysis of readers’ comments in various Greek online mass media, the study examines whether commenters assume any of the core journalistic functions regarding news production, in terms of setting the agenda, providing original information, and airing oppositional views on reported issues. From a public sphere perspective, it also examines the degree of diversity of users’ opinions within media outlets. The results suggest that whereas users challenge journalistic viewpoints to some extent, this type of audience participation is not likely to render audiences co-producers of news content in significant ways or offer opportunities for cross-cutting political exchanges.
Keywords: User-generated content; Participatory journalism; Reader comments; Audience participation